Asistensi Penanaman Adab Menghargai Melalui Pendidikan Agama Islam di SMA Negeri 2 Nuhon - Masrion Tahawali; Anik Mufarrihah; Kusno Setiadi; Dwi Ratna Puspita Sari; Lyra Virginia Usman; Rafly Saril Anugrah (Lembaga Pengembangan Kinerja Dosen, 2025)
Instilling the morality of respect through Islamic Religious Education PAI is an effort to accustom students to respecting others. Instilling this morality of respect aims for students to respect not only teachers or parents, but also friends, the environment, and social values ​​that exist around students. SMA Negeri 2 Nuhon is a place of service. The form of activity is instilling the morality of respect through student participation in PAI learning which goes through the following steps, namely, surveys and coordination with partner schools, developing strategies, and implementing strategies. The results of the service show that most students have implemented the morality of respecting friends and the environment. This instillation needs to be carried out continuously so that it becomes a culture in schools.